(untitled) (Journal of history, 2022)
The article discusses the functions, place and role of beks of clans and tribes in the history of the Golden Horde. From the end of the 14th – beginning of the 15th century, the emirs of local Turkic and Turkicized clans and tribes, striving for independence, began to play an important role in the administrative and political life of the state in comparison with the period before the 15th century. The strengthening of this process is clearly manifested in the XIV – early XV centuries. During this period, the power of emirs and beks, who were the heads of local clans and tribes, and the influence of large tribes that made up the population of the Golden Horde increased. There are numerous medieval sources regarding the historical place and role of the heads of local clans and tribes, who gradually began to play an active role in political life during the heyday of the Golden Horde. Historical information about them is especially widely preserved in the folk memory in the tradition of oral history. Based on the analysis of research papers and information from written and oral literature, the article outlines the functions and role of such beks of clans and tribes in the history of the Golden Horde as Isabek-mangyt, who was the closest associate, nuker of Tokhtamysh, Argyn Karakozha, ulik karasha biy Kutlug-Buk from the Naimans, Ming Alatay, Kiyat Isatay. In the political role of the Golden Horde, we observe a gradual increase in the influence of emirs, tribal beks, who came from representatives of local clans and tribes, the initial stage of the growth of their decisive importance in certain periods. Therefore, the study of the functions of tribal beks makes it possible to consider a number of issues of ethnic history and the socio-political system, domestic and foreign policy from new positions.